2017
DOI: 10.1002/app.44818
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonic acid functionalized siloxane crosslinked with 3‐glycidoxyproyltrimethoxysilane grafted polybenzimidazole high temperature proton exchange membranes

Abstract: Phosphonic acid functionalized siloxane crosslinked with 3‐glycidoxypropyltrimethoxysilane (GPTMS) grafted polybenzimidazole (PBI) membranes are prepared by sol–gel process. The structure of the membranes is characterized by Fourier‐transform infrared spectroscopy and X‐ray diffraction spectroscopy. SEM images of the membranes show that the membranes are homogeneous and compact. The crosslinked membranes exhibit excellent thermal stability, chemical stability and mechanical property. The proton conductivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, the chemical stability could be further improved through grafting or cross‐linking. Kerres J. reported that the cross‐linked PBI membranes have the residual mass value of near 90% after storing in Fenton reagent for 144 h at 68 °C; 3‐glycidoxypropyltrimethoxysilane grafted PBI membrane also shows the oxidative stability with a weight loss of 3.84% after immersion in Fenton's reagent after 48 h at 80 °C . Moreover, polysulfone grafted with sulfonated poly(phenylene sulfide) membrane has a retention ratio of 80% after immersion in Fenton's reagent after 95 h at 80 °C .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the chemical stability could be further improved through grafting or cross‐linking. Kerres J. reported that the cross‐linked PBI membranes have the residual mass value of near 90% after storing in Fenton reagent for 144 h at 68 °C; 3‐glycidoxypropyltrimethoxysilane grafted PBI membrane also shows the oxidative stability with a weight loss of 3.84% after immersion in Fenton's reagent after 48 h at 80 °C . Moreover, polysulfone grafted with sulfonated poly(phenylene sulfide) membrane has a retention ratio of 80% after immersion in Fenton's reagent after 95 h at 80 °C .…”
Section: Resultsmentioning
confidence: 99%
“…PBI-Ph (with rigid group of phenylene) showed higher acid doping levels, less swelling, higher conductivity, and improved mechanical strength, compared to crosslinked PBI-Pr (with non-rigid group of phenylene chain) and the neat PBI membranes. While Qian et al group has incorporated siloxane network with the addition of phosphonic acid in polymer network [88]. Amino trimethylene phosphonic acid (ATMP) were functionalised with 3glycidoxypropyltrimethoxysilane (GPTMS) before grafting onto the PBI backbone.…”
Section: Crosslinking To Improve Membrane Durabilitymentioning
confidence: 99%
“…Many exemplary articles have been reported on this field from both elementary and application contexts. [17][18][19][20] Nonfluorinated PEMs have been extensively scrutinized to moderate the methanol perforation and abstain from the environmental consequence of the fluorinated membrane at the time of preparation. [21][22][23][24] Nonfluorinated PEM constituents are customarily aromatic ring polymers, for instance, sulfonated poly(aryl ether ketone) (SPAEK), 25 sulfonated polysulfone, 26 sulfonated polyethersulfone, 27 and sulfonated polyimide.…”
Section: Introductionmentioning
confidence: 99%
“…Address the challenges of Nafion membranes by developing distinct or modified PEM constituents has been the blazing research theme for this mechanics in past decennium, centralizing on organic and inorganic components to acquire eminent proton conductivity with low water uptake. Many exemplary articles have been reported on this field from both elementary and application contexts 17–20 . Nonfluorinated PEMs have been extensively scrutinized to moderate the methanol perforation and abstain from the environmental consequence of the fluorinated membrane at the time of preparation 21–24 .…”
Section: Introductionmentioning
confidence: 99%